1996
DOI: 10.1111/j.1365-2672.1996.tb03259.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic starter cultures on the organic acid composition of milk and cheese during ripening—analysis by HPLC

Abstract: The major function of lactic starter cultures in cheese making is to produce lactic and other organic acids from the carbohydrates present in milk. The activity of six starter cultures consisting of two Lactococcus lactis ssp. lactis, two Lactococcus lactis ssp. lactis biovar. diacetylactis and two Leuconostoc strains, was tested by monitoring the evolution of the organic acid composition of milk by a modified HPLC method. In addition, their performance as cheese starters was also tested. The HPLC method devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 16 publications
3
45
1
1
Order By: Relevance
“…Pyruvic acid (almost undetectable quantities to 200 mg kg À1 ) represented a steady increase up to 12 days of storage after an initial lag-phase. Some workers have reported, however, that pyruvic acid does not follow any particular trend during maturation of Cheddar and other cheeses, mainly as a result of its role as carbon source for, and intermediate in numerous pathways involved in cheese manufacturing (Larson and Hegarty, 1979;Marsili, 1985;Bevilacqua and Califano, 1992;Bouzas et al, 1993;Gonza´lez de Llano et al, 1996).…”
Section: Organic Acid Fluctuations and Possible Explanationsmentioning
confidence: 94%
See 3 more Smart Citations
“…Pyruvic acid (almost undetectable quantities to 200 mg kg À1 ) represented a steady increase up to 12 days of storage after an initial lag-phase. Some workers have reported, however, that pyruvic acid does not follow any particular trend during maturation of Cheddar and other cheeses, mainly as a result of its role as carbon source for, and intermediate in numerous pathways involved in cheese manufacturing (Larson and Hegarty, 1979;Marsili, 1985;Bevilacqua and Califano, 1992;Bouzas et al, 1993;Gonza´lez de Llano et al, 1996).…”
Section: Organic Acid Fluctuations and Possible Explanationsmentioning
confidence: 94%
“…Orotic, formic, fumaric, uric and hippuric acids as well as diacetyl were detected infrequently in negligible quantities, although considerably higher quantities have been reported in the literature. Gonza´lez de Llano et al (1996) detected hippuric acid in Cheddar cheese, which disappeared rapidly after coagulation suggesting that it could be utilized as a precursor in benzoic acid synthesis. Studies have reported formic and uric acid to either decrease or increase in minute amounts during maturation (Bevilacqua and Califano, 1992;Gonza´lez de Llano et al, 1996).…”
Section: Organic Acid Fluctuations and Possible Explanationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Increases of 24.25% Ϯ 5.57% and 48.36% Ϯ 7.79% in yctCBA promoter expression were obtained for RTS and FBS, respectively. High-performance liquid chromatographic (HPLC) analysis of both sera was performed by the method of González de Llano et al (17) using an ionic exclusion column ICSep ION-300 (Transgenomic, San Jose, CA) loaded with 100 l of a serum sample that had previously been diluted 10-fold and filtered (0.45 m). Citric acid elution occurred at 14 min, and quantification was performed by using a linear regression equation (R 2 Ն 0.99) using citric acid at different concentrations as a standard.…”
mentioning
confidence: 99%